Pattern of skin diseases and common drugs prescribed in dermatology outpatient department of Kathmandu Medical College-Teaching Hospital, Duwakot - Shrestha, Binaya; Shrestha, Prashanna Raj (Journal of Kathmandu Medical College, 2020)
Background: There is a wide variation in the pattern of skin diseases in different countries and the pattern even varies across different parts within the same country. For the treatment purpose different classes of drugs and combinational products are widely used in dermatology. Periodic prescription analysis in the form of drug utilization study can improve the quality of prescription and decrease irrational prescribing.Objectives: The objective of the study was to find the pattern of skin diseases and the common group of drugs prescribed in Kathmandu Medical College Teaching Hospital at Duwakot.Methodology: A prospective, observational, single center study was conducted at Dermatology outpatient department of Kathmandu Medical College Teaching Hospital at Duwakot, from December 2018 to June 2019 and a total of 300 prescriptions were collected during the study period. The data were collected from patient card and details were filled in the predesigned proforma.Results: A total of 300 prescriptions were collected and analyzed for demographic profile, disease incidence and drug prescription. Most common condition observed were dermatitis 50 (16.7%), tinea 43 (14.3%), urticaria 31 (10.3%). Antihistaminics (28.7%), corticosteroids (16.9%) antibiotics (14.8%), antifungals (14.8%) were the most common class of drugs prescribed. Drugs prescribed were mainly given by topical route (50.6%) followed by oral route.Conclusion: The current study revealed that the mean number of drugs/prescriptions was slightly higher than the recommended limit of two approved by world health organization and the practice of poly-pharmacy was occasionally seen.